Crystalline CdS/MoS2 shape-controlled by a bacterial cellulose scaffold for enhanced photocatalytic hydrogen evolution. (15th December 2020) - Jiang, Shan; Hu, Qiang; Xu, Mengying; Hu, Shengjun; Shi, Xiao-Chen; Ding, Ran; Tremblay, Pier-Luc; Zhang, Tian
Graphical abstract: Highlights: Berry-shaped (b) CdS was synthesized with bacterial cellulose (BC) as a scaffold. BC affects the size and morphology of b-CdS during hydrothermal synthesis. A heterojunction photocatalyst was fabricated combining b-CdS and MoS2 . b-CdS/1%MoS2 had an excellent photocatalytic activity with 63.59 mmol H2  g −1  h −1 . Abstract: The conversion of sunlight into H2 by noble-metal-free photocatalysts is a promising approach for the production of easy-to-store chemical energy. For this purpose, higher efficiency is achieved by photocatalysts with heterojunctions preventing fast charge recombination. Most processes for the synthesis of high-performance heterojunction photocatalysts require solvents harmful to living organisms. Here, berry-shaped (b)-CdS/MoS2 particles were fabricated instead by a hydrothermal process where non-toxic bacterial cellulose was used to mold b-CdS into nanostructures with enhanced spatial arrangement. Subsequently, MoS2 was combined with b-CdS resulting in a composite with suitable shape and intimate semiconductor contacts beneficial for charge transfer. The photocatalytic H2 evolution (PHE) of b-CdS/1%MoS2 was 63.59 mmol g −1  h −1 . It was 61.1 times, 397 times, and 10.2 times higher than PHE with b-CdS, CdS fabricated without BC scaffold, and b-CdS doped with Pt, respectively. These results show the high potential of b-CdS/MoS2 and the associated synthesis method for PHE.